TIME VALUE OF MONEY DALAM PERSPEKTIF EKONOMI ISLAM - Yuliono Yuliono (Fakultas Ekonomi dan Bisnis Islam (FEBI), Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2017)
Abstract The time value of money is associated with the current value and future value because the money received now is more worth than the money received in the future. However, is the concept of time value of money is appropriate and justified by the Shari'ah? The time value of money is a concept that says that the money of the one rupiah that can be received today is more worth than one rupiah which will be received in the future time. The concept of time value of money is needed by financial managers in making decision when will invest in an asset and determine the source of loan funds that will be chosen. Islam views money as a flow concept. Money must rotate in an economy and may not be idle for too long time. Moreover, it lets for years. Islam does not recognize the method of time value of money because this method adds value to money solely with increasing time and not effort. Islam actually knows the money value of time; that is the time has economic value as well as the money value of money. Imam Nawawi provides definition related to value addition for money based solely on the value of time is the category of riba.